Hydroponic Innovation: The Effect of Magnetic Field Treatment on Water on Vegetable Growth - Tsehai, Kibebew; Odote, Jackson Maxwell (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: Determine the effect of the implications of water processed by magnetic fields on the growth of vegetable seeds by farming using a hydroponic system and the physical properties of the water (including pH, temperature, conductivity). Methodology: This study used a laboratory experimental design with a power supply (1–3 A), PVC pipe, and 0.7 mm enamel wire to generate a magnetic field. Measuring instruments included a digital pH meter, a digital thermometer, and a digital conductivity meter. Statistical analysis was performed using SPSS 16.0 for Windows with a one-way ANOVA test. The hydroponic media were cotton and water from the Regional Drinking Water Company, with caisim, pak choi, and lettuce seeds. Main Findings: The water treated with a magnetic field showed significant changes in pH and conductivity, while the temperature remained stable due to environmental influences. Hydroponic growth showed good results for Chinese cabbage and lettuce, while pak choi yielded less than optimal results. This variation is directly related to the suitability of the magnetically treated water for supporting nutrient absorption and plant physiological processes. Novelty/Originality of this study: This research provides new insights into the role of magnetic field treatment on water properties and its implications for hydroponic farming. Unlike previous research, this study highlights the specific responses of vegetables to magnetized water, demonstrating its potential to improve growth efficiency in certain crops. These findings contribute to sustainable agricultural practices and offer a low-cost innovation for increasing hydroponic productivity.